2016
DOI: 10.1186/s12879-016-1603-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bacterial pathogens associated with acute diarrhea in children under 5 years of age: a hospital-based cross-sectional study

Abstract: BackgroundAcute diarrhea is a leading cause of morbidity and mortality in children, particularly in those under the age of 5 years. Rotavirus is recognized as the leading cause of acute diarrhea in children, however, the contribution of bacterial pathogens as causative agents varies throughout the world. Here we report a hospital-based prospective study to analyze the characteristics of bacterial pathogens associated with acute diarrhea in children under 5 years of age.MethodsStool samples were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
2
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 34 publications
(36 reference statements)
4
30
2
9
Order By: Relevance
“…Researchers have also reported that early oral rehydration and nutrition have been shown to be the main interventions in management of diarrhea [6]. For example, oral rehydration therapy/solution (ORS), the most common approach for management of diarrhea, prevents about three million dehydrationrelated deaths in a year [7]. Recently, the most important goal in management of acute diarrhea is rehydration therapy to correct fluid, glucose, and electrolyte deficits in the body [8].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also reported that early oral rehydration and nutrition have been shown to be the main interventions in management of diarrhea [6]. For example, oral rehydration therapy/solution (ORS), the most common approach for management of diarrhea, prevents about three million dehydrationrelated deaths in a year [7]. Recently, the most important goal in management of acute diarrhea is rehydration therapy to correct fluid, glucose, and electrolyte deficits in the body [8].…”
Section: Introductionmentioning
confidence: 99%
“…35 Over the past few years, the dissemination of PMQR genes among quinolone-resistant Shigella isolates has been surveyed in some studies and has emerged as an important issue across the world. [36][37][38][39] It has been reported that aac(6')-Ib-cr signi cantly increases the frequency of selection of chromosomal mutants to reduce cipro oxacin activity by N-acetylation at the amino nitrogen on its piperazinyl substituent. 40 The aac(6')-Ib-cr-positive Shigella was rst isolated in 1998; 41 however, the most striking nding of our previous and present study was the aac(6′)-Ib-cr allele wide penetration in all quinolone-resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The toxin intern produced by this bacterium can cause injury to the mucosa and ultimately bloody stools. 23,24 Breastmilk inhibits the growth of the bacteria and thus tend to have less severe symptoms than non-breastfed babies In patients with diarrhea, a stool pH level of 5.5 or less or presence of reducing substances indicates carbohydrate intolerance, which is usually secondary to viral illness and transient in nature. 25…”
Section: Discussionmentioning
confidence: 99%